2001
DOI: 10.1046/j.1365-2281.2001.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

A new method to quantify postexercise ST‐deviation – the ST‐deficit. A study in men at high and low‐risk for coronary heart disease

Abstract: Effort-related myocardial ischaemia is frequently silent in elderly high-risk hypertensives and necessitates testing, preferably with computerized exercise ECG and heart rate adjusted ST criteria. A new quantitative variable to assess the postexercise rate-recovery loop in the time domain, the ST-deficit is described. This variable seems to effectively discriminate between subjects with low and high-risk for coronary heart disease and thus provides new information. Further studies are warranted to validate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…Other researchers have also shown ST/HR analysis integrating exercise and recovery to improve the diagnostic capacity of exercise ECG [15][16][17][18]. However, the majority of patients in the previous studies have been men, and hitherto the diagnostic performance of ST/HR hysteresis in women has been unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have also shown ST/HR analysis integrating exercise and recovery to improve the diagnostic capacity of exercise ECG [15][16][17][18]. However, the majority of patients in the previous studies have been men, and hitherto the diagnostic performance of ST/HR hysteresis in women has been unknown.…”
Section: Discussionmentioning
confidence: 99%
“…, 2005). The quantification of ST/HR loops can be obtained by calculation of the difference between the ST‐segment amplitude during recovery phase and the ST‐segment amplitude at the corresponding HR during exercise (Suurküla et al. , 2001; Kronander et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 1989; Lehtinen et al. , 1996; Suurküla et al. , 2001) offers yet another diagnostic possibility, with performance superior to both that of ST/HR index and ST/HR slope.…”
Section: Introductionmentioning
confidence: 99%
“…However more recent studies showed that low amplitude T-wave alternans discriminates patients with ventricular tachycardia (VT) or ventricular fibrillation (VF) from those without VT or VF [Rosenbaum et al, 1996]. The analysis of the ST-segment is a standardized method of ECG analysis, but surprisingly no variability of this segment has been considered so far [Lehtinen et al, 1996;Suurkula et al, 2001]. There are two types of ST-T wave abnormalities which are very common and may be seen in any lead of the ECG: an ST segment depression and an ST segment elevation.…”
Section: State Of the Art In Clinical Practicementioning
confidence: 99%